1982
DOI: 10.1089/hyb.1.1982.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Against Human Fibronectin Which Inhibits Cell Attachment

Abstract: Monoclonal antibodies have been prepared against both human and bovine fibronectin. Evidence is provided which indicates that nine different antigenic determinants are recognized by the ten antihuman fibronectin monoclonal antibodies isolated. One monoclonal antibody was identified that blocked fibronectin mediated cell attachment without interfering with fibronectin binding to collagen. Sensitive ELISA assays for fibronectins derived from 32 mammalian species have been developed with the monoclonal reagents c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 24 publications
0
63
0
Order By: Relevance
“…2, region 2 and integrin-binding sites on adjacent monomer). This may relate to the observation that, at least for certain cell types, one mode of attachment to native type I collagen is fibronectin-dependent and is mediated by these integrin receptors (34). Moreover, the site of binding of the decorin core protein (35), which has been shown to interact with fibronectin (36), is also adjacent to several of the integrin-binding sites (19) (Fig.…”
Section: Distribution Of Ligand-binding Sites and Functional Domains mentioning
confidence: 97%
“…2, region 2 and integrin-binding sites on adjacent monomer). This may relate to the observation that, at least for certain cell types, one mode of attachment to native type I collagen is fibronectin-dependent and is mediated by these integrin receptors (34). Moreover, the site of binding of the decorin core protein (35), which has been shown to interact with fibronectin (36), is also adjacent to several of the integrin-binding sites (19) (Fig.…”
Section: Distribution Of Ligand-binding Sites and Functional Domains mentioning
confidence: 97%
“…40,41 The antibody used (HFN7.1) was directed against the flexible linker between the 9 th and 10 th type III repeats of FN. 42 The antibody mAb1937 is directed against the 8 th type III repeat of FN. It has been previously demonstrated that HFN7.1 is a receptor-mimetic probe for integrin binding and cell adhesion.…”
Section: à2mentioning
confidence: 99%
“…2C,F); fibroblasts seeded on FNIII 8,9,10 cross-linked glass (or plastic) remained spread in the presence or absence of TGF-β treatment (data not shown). As a complementary approach, we also pre-incubated pFNPAGs with HFN7.1, a monoclonal antibody that binds to the synergy site in FNIII 9 [16,17]. In contrast to control cultures, we observed that fibroblast contraction was inhibited and the cells retained a spread morphology in the presence of TGF-β (Fig.…”
Section: The Synergy/cell Binding Domain In Fn III 8-10 Supports Fibrmentioning
confidence: 97%